Somewhere in between grammar and lexis: the role of verb types in learner production of caused-motion constructions - Rosa, Rodrigo Garcia (The ESPecialist, 2025)
This article deals with the selection, extraction and analysis of learner written production of English caused-motion constructions. The data extraction targeted four groups of learners with regard to their L1s (Brazilian Portuguese, Spanish, Italian and French) and their levels of English proficiency (from A1 to C2 in the CEFR). The data were extracted from EFCamDAT corpus, a morpho-syntactically tagged corpus of learner written production. The analysis targets the lexical variability in the production of learners across levels of proficiency and with different L1s so as to verify the extent to which we can claim learners have access to schematic caused motions or whether they appeal to specific verb classes, namely, instantiation and modification verbs. The results, especially the quantitative ones, indicate a strong reliance on verbal over constructional knowledge in the production of English caused-motion structures. The study also sheds light on developmental factors involving the relationship between grammar and lexis.